Shallow distance-dependent triplet energy migration mediated by endothermic charge-transfer - Runchen Lai (Nature Communications, 2021)
Spin-triplet energy transfer in molecular systems underlies important applications for chemistry and devices. Here, the authors investigate the triplet energy transfer in CdSe quantum dots with varying ZnS shell thicknesses to surface-anchored anthracene molecules and identify a stepwise mechanism mediated by endothermic charge-transfer states.